Wyznaczanie oczekiwanej realnej stopy procentowej w Polsce z wykorzystaniem modelu przestrzeni stanów - Stelmach, Jerzy (Determining the Ex Ante Real Interest Rate in Poland Using State-Space Model, 2007)
The ex ante real interest rate - the difference between nominal rates and expected inflation - is a crucial variable in economic decision-making process. Due to nonobservability of expected inflation rate, appropriate measuring of ex ante real interest rate encounters certain difficulties. In this paper, a state-space model was employed in order to estimate unobserved expected real interest rate in Poland between 1999 and 2005. The obtained results are used to verily well-known Fisher effect.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 148-157